Environmental Health Literacy and Climate Change Anxiety Among Teachers: The Mediating Role of Ecological Footprint Awareness - Açıkgöz, Özge; Soylar, Pınar (Multidisciplinary Digital Publishing Institute (MDPI), 2026)
Background: Environmental health literacy plays an important role in helping individuals recognize environmental risks and adopt sustainable behaviors. Increasing environmental awareness may also influence emotional responses to environmental problems such as climate change. However, the mechanisms linking environmental health literacy to climate change anxiety remain insufficiently explored. This study aimed to examine the relationship between environmental health literacy and climate change anxiety among teachers and to evaluate the mediating role of ecological footprint awareness in this relationship. Methods: This cross-sectional study was conducted with teachers working in public schools in the provinces of Elazığ and Erzincan, Türkiye. Data were collected using a personal information form, the Environmental Health Literacy Scale, the Ecological Footprint Awareness Scale, and the Climate Change Anxiety Scale. Descriptive statistics, group comparison tests, correlation analyses, and mediation analysis based on structural equation modeling were performed to examine the relationships among the study variables. Results: Participants’ mean scores were 35.98 ± 9.12 for the Climate Change Anxiety Scale, 95.37 ± 18.29 for the Environmental Health Literacy Scale, and 118.08 ± 25.92 for the Ecological Footprint Awareness Scale. Environmental health literacy was positively associated with ecological footprint awareness, and ecological footprint awareness was positively associated with climate change anxiety (p < 0.001). Mediation analysis indicated that ecological footprint awareness significantly mediated the relationship between environmental health literacy and climate change anxiety (β = 0.293, 95% CI: 0.112–0.496, p = 0.002). Conclusions: The findings suggest that ecological awareness can serve as a potential mechanism linking environmental knowledge with emotional responses to climate change. Strengthening ecological footprint awareness through environmental education programs for teachers may contribute to both environmental awareness and constructive engagement with climate-related issues. © 2026 by the authors.
Keywords: Climate Change Anxiety; Ecological Footprint Awareness; Environmental Health Literacy; Mediation Analysis; Teachers